Kreativitas Group Musik Dangdut Pro Divana Remabang - -, joko wiyoso (Universitas Negeri Semarang, 2018)
Creativity is essentially the ability of a person to produce something new, both in the form of ideas and real work, both in the form of new works. Can be a group or a community that in the process of art can create new things. The research method used in this study is qualitative descriptive. Data collection techniques by observation, interviews and documentation studies with data validity techniques are data triangulation. The results of this study are the creativity of the Dangdut Pro Divana music group in Rembang implementing 4 stages, namely (1) Preparing (preparation), creative preparation of Pro Divana. (2) Incubation (incubation), Pro Divana is dangdut which is one of the entertaining dangdut for dangdut music fans. (3) llumunitasion (illumination), in addressing fans of Dangdut Music, by asking Pro Divana to bring foreign songs to be heard. (4) Verification (verification), from the results conducted by Pro Divana is to add material to dangdut songs. Based on the results of research and discussion, the creativity of pro divana aims to develop their musicality in music and give a different nuance to dangdut music fans in enjoying dangdut songs.